2019
DOI: 10.1136/bmjopen-2019-031874
|View full text |Cite|
|
Sign up to set email alerts
|

Emerging cancer incidence, mortality, hospitalisation and associated burden among Australian cancer patients, 1982 – 2014: an incidence-based approach in terms of trends, determinants and inequality

Abstract: ObjectiveCancer is a leading killer worldwide, including Australia. Cancer diagnosis leads to a substantial burden on the individual, their family and society. The main aim of this study is to understand the trends, determinants and inequalities associated with cancer incidence, hospitalisation, mortality and its burden over the period 1982 to 2014 in Australia.SettingsThe study was conducted in Australia.Study designAn incidence-based study design was used.MethodsData came from the publicly accessible Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…It could be explained by the fact that hospitalization costs were very high. Medical expenses (including medicines and treatments) and non-medical costs (including transportation, caregiver costs, lost productivity, and loss/reduction of household income) in inpatient services were higher than those in outpatient visits, which exacerbated the burden on health care use ( 31 33 ). Hence, cancer patients from socioeconomically disadvantaged households could not afford the high medical costs; actually, they tended to abandon medical services or sought cheaper outpatient services instead of inpatient services ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It could be explained by the fact that hospitalization costs were very high. Medical expenses (including medicines and treatments) and non-medical costs (including transportation, caregiver costs, lost productivity, and loss/reduction of household income) in inpatient services were higher than those in outpatient visits, which exacerbated the burden on health care use ( 31 33 ). Hence, cancer patients from socioeconomically disadvantaged households could not afford the high medical costs; actually, they tended to abandon medical services or sought cheaper outpatient services instead of inpatient services ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is the most significant global public health problem and a leading cause of death and illness in the world in the 21st century, including Australia [30]. Breast cancer is estimated to have been the most commonly diagnosed cancer in 2019, followed by prostate cancer.…”
Section: Cancermentioning
confidence: 99%
“…Mahmud et al [30] used multivariate analysis to analyze the trends associated with cancer incidence, hospitalization, and fatality for several barriers. The study was conducted for the period 1982-2014 and the results revealed that socio-economic and geographical access play a significant role in patient outcome.…”
Section: Cancermentioning
confidence: 99%
“…Breast and ovarian cancer are amongst the most common female malignancies, with a history of breast cancer linked to a higher risk of ovarian cancer ( Mahumud et al, 2019 ). Recent advances in medical science, including earlier detection and targeted treatments, have significantly increased survival in many cancers, including breast and ovarian ( Matchett et al, 2017 ; Prakash et al, 2018 ; Siegel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%